2010
DOI: 10.2478/v10101-010-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Core stability of male and female football players

Abstract: SummaryStudy aim: To investigate into core stability measures and to establish the preliminary normal data. Material and methods: Three groups of football players were studied: male players, members of an amateur club (Division IV; n = 20), female players, members of a Division I club (n = 28) and male adolescent club players (n = 17). They were subjected to 4 tests of core stability (muscular endurance of trunk flexors and extensors, and of left and right lateral bridge) at the beginning of the 2009/2010 seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…trunk flexed) which overloads the low back. This condition requires a high level of endurance of core muscles to improve spine stabilization, minimize compression overload and prevent injuries [22]. However, in the present study, the hockey athletes showed endurance levels below the average proposed by McGill [21] for all tests measured (prone bridge, lateral bridges, flexor endurance, and extensor endurance).…”
Section: Discussioncontrasting
confidence: 48%
“…trunk flexed) which overloads the low back. This condition requires a high level of endurance of core muscles to improve spine stabilization, minimize compression overload and prevent injuries [22]. However, in the present study, the hockey athletes showed endurance levels below the average proposed by McGill [21] for all tests measured (prone bridge, lateral bridges, flexor endurance, and extensor endurance).…”
Section: Discussioncontrasting
confidence: 48%
“…This explains the interest of coaches [15] and physical therapists [8] in such exercises. Especially in low back pain (LBP) prevention, abdominal exercises should be performed in positions that prevent overload to the lumbar region of the vertebral column.…”
Section: Introductionmentioning
confidence: 99%
“…The players of the defensive team are: linebackers, ends, defensive tackles, cornerbacks and safeties [25]. American football requires exceptional abilities and the development of physical qualities [26,40].…”
Section: Introductionmentioning
confidence: 99%